PENINGKATAN HASIL BELAJAR LUAS JAJARGENJANG DAN SEGITIGA DENGAN PENDEKATAN COOPERATIVE LEARNING TIPE STUDENT TEAMS ACHIEVEMENT DIVISION DI SEKOLAH DASAR - Syakdan, Anna Ilfani (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
For that action research was held with the aim of describing the vast improvement of learning outcomes parallelogram and a triangle with type STAD Cooperative Learning Approach in the Elementary School Fourth Grade 14 Payakumbuh. The results of each cycle performed has increased. Seen at: a) Planning learning first cycle 77%, while the second cycle of 88%. b) The study of the research cycle I and cycle 71% II 89%. While the students' first cycle of 56% and 86% the second cycle. c) student learning cycle I 66.76 and cycle II 77.97. Kata Kunci: hasil belajar, luas jajargejang dan segitiga, student teams achievement divisions